2×2+14x=0

Factor 2x out of 2×2.

2x(x)+14x=0

Factor 2x out of 14x.

2x(x)+2x(7)=0

Factor 2x out of 2x(x)+2x(7).

2x(x+7)=0

2x(x+7)=0

Divide each term in 2x(x+7)=0 by 2.

2x(x+7)2=02

Simplify 2x(x+7)2.

Cancel the common factor of 2.

Cancel the common factor.

2x(x+7)2=02

Divide x(x+7) by 1.

x(x+7)=02

x(x+7)=02

Apply the distributive property.

x⋅x+x⋅7=02

Simplify the expression.

Multiply x by x.

x2+x⋅7=02

Move 7 to the left of x.

x2+7x=02

x2+7x=02

x2+7x=02

Divide 0 by 2.

x2+7x=0

x2+7x=0

Factor x out of x2.

x⋅x+7x=0

Factor x out of 7x.

x⋅x+x⋅7=0

Factor x out of x⋅x+x⋅7.

x(x+7)=0

x(x+7)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x=0

x+7=0

Set the first factor equal to 0.

x=0

Set the next factor equal to 0.

x+7=0

Subtract 7 from both sides of the equation.

x=-7

x=-7

The final solution is all the values that make x(x+7)=0 true.

x=0,-7

Solve using the Square Root Property 2x^2+14x=0